An Innovative Approach to Stakeholder Theory: application in spanish transnational corporations - Retolaza, Jose Luis; Ruiz-Roqueñi, Maite; San-Jose, Leire (Review of Business Management, 2015)
Objective – This paper describes a different perspective on the application of stakeholder theory, concentrating only on the interests of stakeholders rather than on their roles. The purpose of this article is to provide an option for solving Jensen’s “problem of governance”; this approach will allow the agent to manage the stakeholders having ascertained that the needs of stakeholders overlap and, accordingly, the agent should be able to monitor multiple stakes as they are aligned. Design/methodology/approach – A Delphi method was used with the aim to achieve consensus about the interests of stakeholders for companies in Spain. The confirmatory phase was based on interviews to test whether the interests identified in the preliminary study match the interests that the IBEX-35 firms recognized in relation with their stakeholders. Findings – The main contributions are: the addition of a new interestbased perspective to the different classifications made by stakeholder theory; a solution to the diversity of indicators between stakeholders and shareholders; and, finally, a proposal for an integrated accounting system, incorporating economic as well as social issues employing a common metric (monetary). Practical implications – A new perspective focusing on stakeholder interests and the confirmation that interests may converge permits the control and management of multiple principals in transnational corporations operating in different countries. Originality/value – There is a gap in the applicability of stakeholder management that the interest-based perspective can help resolve; moreover the monetization of social value is an option to efficiently manage transnational corporations.